Sugarcane growth in India: Problems and prospects: Sugarcane growth in India: Problems and prospects - Arun, JV; Premkumar , A (SAARC Journal of Agriculture, 2022)
Sugarcane is one of the most important cash crops in India. India being a major consumer of sugar occupies the second place in sugarcane production, next to Brazil. In recent times, sugarcane has become a preferred crop for renewable and eco-friendly energy production. Excepted rise in demand for energy has improved the scope of sugarcane production. In this backdrop, the study focuses on the trend and growth of production area, production and productivity of sugarcane crop in India for the period 2001-02 to 2017-18. The relationship between harvested area and production is tested with the help of a regression model. Apart from that, the study analyzes the state wise growth rate of sugarcane sector. The study is based on secondary data collected from various government reports and publications. The result highlights that all the three variables under consideration witness positive growth rate. About 65% of the production comes from two states, Uttar Pradesh and Maharashtra. Comparatively states falling under tropical region have higher yield per hectare than states of sub-tropical region. Finally, to an extent, this paper suggests ways to improve sugarcane productivity. SAARC J. Agric., 20(2): 133-144 (2022)